Visible Light Optical Coherence Tomography: Technology and Biomedical Applications - Songzhi Wu; Shuo Wang; Baihan Li; Zhao Wang (Bioengineering)
Compared to widely used near-infrared OCT (NIR-OCT) systems, visible light OCT (vis-OCT) is an emerging imaging modality that leverages visible light to achieve high-resolution, high-contrast imaging and enables detailed spectroscopic analysis of biological tissues. In this review, we provide an overview of the state-of-the-art technology development and biomedical applications of vis-OCT. We also discuss limitations and future perspectives for advancing vis-OCT.